MENGENAL KAMPANYE KOMUNIKASI - Sumaina Duku (Wardah, 2013)
This article aimed to describe communication campaign in social field include planning, process, and evalution. Communication campaign is a coodinated use of different methods of communication aimed at focusing attention on particular problem and its solution over a period of time. Public communication campaign as purposive attempt to inform, persuade, or motivate behavior changes in a relatively well-defined and large audience, generally for noncommercial benefits to the individual and/or society, typically within a given time period, by means of organized communication activities involving mass media and often complemented by interpersonal support.